Relationship Between Motivation and Performance of Posyandu Cadres - wijayanti, Novi; Vanchapo, A.R; Darmayanti, Aquartuti Tri (Journal of World Future Medicine, Health and Nursing, 2023)
Motivation is a process that occurs in a person that appears with feelings so that it encourages individuals to do something caused by one's desires, needs and goals. The performance of cadres can be seen from the success of a cadre in carrying out their duties. To improve the performance of posyandu cadres, the ability of a cadre must be developed. The purpose of this study was to determine the relationship between work motivation and the performance of posyandu cadres. The database used in the Literature review is Google Scholar with sample inclusion criteria, articles published in the last 5 years, using national journals, articles using the correlational method with the population used are Posyandu cadres. The search  for  journals  in  this  study used the search keyword "Motivation AND performance of Posyandu cadres". The results and analysis obtained as many as 4.580 articles were identified, the researcher found 10 articles that could be used in the literature review. Based on the results of the review that motivation has the effect of increasing the performance of cadres.